A Systematic Review of the Educational Effectiveness of Simulation Used in Open Surgery - Simms, Ciaran (My University, 2019)
The role of simulation to teach and access open surgical skills has become more prevalent in recent years. This systematic review synthesizes the totality of evidence with respect to the educational effectiveness of simulators used in open surgical training. A systematic literature search was conducted in PubMed, Embase, CINAHL, Scopus, and Web of Science. Only randomized controlled trials were included that explored the educational efficacy of theses simulators. Six randomized controlled trials were included from the 9934 studies found. The methodological quality of the included studies was variable. Overall, the use of the simulators was more educationally effective compared with standard teaching of the skill without a simulator (P < 0.05). Two studies showed that the simulator was as good as an animal model of much higher fidelity. Further studies are needed to secure higher evidence for the educational value, validity, and transferability of the skills to the hospital setting for all simulators.
Keywords: hospital setting; systematic review synthesize; simulators